Detection of mixed Mycobacterium tuberculosis infections in South African TB Patients - Stead, Michael Craig (Division of Medical Microbiology, 2014)
Recently, the widely accepted theory that TB disease resulted from one infecting M. tuberculosis strain leading to heightened immune protection against subsequent infections, has been revised. Epidemiological studies and the advances in molecular genotyping techniques have highlighted the rapidly frequent isolation of several different M. tuberculosis strain lineages in single disease episodes, often with differing drug susceptibilities. This has important implications on drug susceptibility testing and the treatment of patients. It has also highlighted the relative contributions of exogenous reinfection and endogenous reactivation in TB disease progression. However, our understanding of the nature and frequency of mixed infections is lacking. This study investigated the frequency and detection of mixed TB infections in the Delft region of the Western Cape, as part of a larger clinical trial on the effects of multi-nutrient supplementation and standard treatment on the TB bacteriological response. Newly diagnosed, adult TB patients (n=154) produced a single weekly sputum sample over an 8-week period. Genomic DNA was extracted from colonies grown from MGIT cultures on LJ slopes. Spoligotyping was used as an initial screen to detect mixed infections as well as to assess the epidemiology of M. tuberculosis in these serial isolates (n=686). In addition, clonal relatedness of the isolates was assessed by MIRU-VNTR analysis. Thereafter PCR assays to detect infections of W-Beijing and non-W-Beijing isolates, as well as to differentiate mixed non-W-Beijing isolates were carried out. Phenotypic and genotypic drug susceptibility was carried out. Spoligotyping indicated that W-Beijing isolates constituted a large proportion (47.8%) of circulating M. tuberculosis in this region, with other strains detected including LAM (17.1%), T (14.7%), X (6.4%), H (7.9%), S (4.3%), and F33 (2.1%) strains. Using both spoligotyping and PCR assays, mixed infections were detected 21 (16.3%) of 129 patients screened. Phenotypic and genotypic DST confirmed that all isolates identified in patients as harbouring mixed strains by spoligotyping were fully susceptible to both RIF and INH. MIRU-VNTR 2 analysis for genetic relatedness identified 1 clonal cluster in the mixed samples identified by spoligotyping, consisting of the T1, T4, W-Beijing and W-Beijing + X3 isolates. The frequency of mixed infections, particularly in high disease burdened areas, is high, and warrants further attention. This finding has great implications with regards to the interpretation of epidemiological and DST data, and the subsequent treatment of patients.